APPLICATION OF BALANCED SCORECARD IN PERFORMANCE ASSESSMENT IN THE REPUBLIC OF INDONESIA EMPLOYEE COOPERATIVE (KP-RI) BAKTI HUSADA BARRU DISTRICT - Mahmud, Usamah; Muliati; Indriani (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal